(untitled) (Journal of Parents and Teachers, 2026)
Terrorism is a persistent historical reality, a constant experience and threat to coexistence, a challenge, with personal stories of its protagonists and victims that fill us with questions about how they experience it and what their situation might be like. This article aims, above all, to move from knowledge of specific situations of terrorism to knowledge of the motives behind all types of terrorist actions, bringing us a little closer to the reality of human injustice and other injustices that seek to replace it. Albert Camus’s work ‘The Just’ is key to understanding terrorism.